2016
DOI: 10.1042/bcj20160219
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase catalyses the N-methylation of the endogenous β-carboline norharman: evidence for a novel detoxification pathway

Abstract: Nicotinamide N-methyltransferase (NNMT) is responsible for the N-methylation of nicotinamide to 1-methylnicotinamide. Our recent studies have demonstrated that NNMT regulates cellular processes fundamental to the correct functioning and survival of the cell. It has been proposed that NNMT may possess β-carboline (BC) N-methyltransferase activity, endogenously and exogenously produced pyridine-containing compounds which, when N-methylated, are potent inhibitors of Complex I and have been proposed to have a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 58 publications
(119 reference statements)
0
29
0
Order By: Relevance
“…Previous studies revealed norharmane to be a weak substrate for NNMT with a K M value of 90 µM, significantly lower than that of the native substrate NA (K M 200 µM), but with a very low turnover rate. 22 We were therefore interested in assessing whether such a strong binding, slowly converted NNMT substrate might in fact act as an inhibitor by occupying the NNMT active site. 16,22 Indeed, it was found that norharmane inhibits NNMT with an IC 50 of 115.3 ± 20.6 µM.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed norharmane to be a weak substrate for NNMT with a K M value of 90 µM, significantly lower than that of the native substrate NA (K M 200 µM), but with a very low turnover rate. 22 We were therefore interested in assessing whether such a strong binding, slowly converted NNMT substrate might in fact act as an inhibitor by occupying the NNMT active site. 16,22 Indeed, it was found that norharmane inhibits NNMT with an IC 50 of 115.3 ± 20.6 µM.…”
Section: Articlementioning
confidence: 99%
“…22 We were therefore interested in assessing whether such a strong binding, slowly converted NNMT substrate might in fact act as an inhibitor by occupying the NNMT active site. 16,22 Indeed, it was found that norharmane inhibits NNMT with an IC 50 of 115.3 ± 20.6 µM. The low K M is offset by a diminished turnover rate giving norharmane the ability to occupy the NNMT active site and effectively block the methylation of nicotinamide.…”
Section: Articlementioning
confidence: 99%
“…These studies have been extensively cited in the literature to justify the identification of NNMT as responsible for the N-methylation of a range of pyridine-containing compounds such as quinolines and β-carbolines (Parsons et al, 2002(Parsons et al, , 2003Williams and Ramsden, 2005). Our recent studies have shown that the majority of these are poor NNMT substrates, with only isoquinoline demonstrating a catalytic efficiency (k cat /K m ) value greater than 30% of that observed for nicotinamide (van Haren et al, 2016;Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…The unsubstituted 1,2,3,4‐tetrahydro‐ β Cs and the unsubstituted full‐aromatic nor harmane (9H‐pyrido[3,4‐b]indole; nHo) crosses the blood–brain barrier penetrating into the brain . Inside the brain, nHo is converted by certain S‐adenosyl methionine‐dependent N‐methyltransferases to the N‐methyl‐ β C cation named 2‐methyl‐ nor harmanium (2‐Me‐nHo) and subsequently to the 2,9‐dimethyl‐ nor harmanium cation (2,9‐diMe‐nHo) .A broad spectrum of biological activity has been reported for N‐methyl‐ β Cs (quaternary βCs): (1) They were described as potential pathogenetic factors in Parkinson's disease . The main mechanism through which these alkaloids would exert their effect still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The unsubstituted 1,2,3,4-tetrahydro-bCs and the unsubstituted full-aromatic norharmane (9H-pyrido [3,4-b]indole; nHo) crosses the bloodbrain barrier penetrating into the brain (21,22). Inside the brain, nHo is converted by certain S-adenosyl methionine-dependent N-methyltransferases to the N-methyl-bC cation named 2-methylnorharmanium (2-Me-nHo) and subsequently to the 2,9-dimethylnorharmanium cation (2,9-diMe-nHo) (23).…”
Section: Introductionmentioning
confidence: 99%